Synthesis of MnCoO/CNT nanoflakes for the photocatalytic degradation of methyl orange dye and the evaluation of their activity against Culex pipiens larvae in the purification of fresh water. Issue 45 (12th October 2022) - Mohamed, Rania A.; Ghazali, Niveen M.; Kassem, L. M.; Elgazzar, Elsayed; Mostafa, Wageha A.
Abstract : Researchers worldwide have been looking forward to using novel ways to purify fresh water containing pollutants and disease vectors. Abstract : Researchers worldwide have been looking forward to using novel ways to purify fresh water containing pollutants and disease vectors. In the current work, nanoparticles were introduced as a promising technique for cleaning water and saving human health and living organisms. The nanocomposites, MnCoO and MnCoO/CNTs, were fabricated by a cost-effective co-precipitation method. Phase and molecular structures were investigated by XRD and Raman spectroscopy. The samples exhibited polycrystalline nature of binary phase and weak crystallinity. The elemental composition was recorded by EDX spectra, revealing the purity of the nanoparticles. The surface morphology and particle distribution were described using SEM and TEM micrographs, indicating that MnCoO/CNTs are nanoflakes with a large surface area. The optical parameters include α, E g, n, k, which were identified from T % and R % measurements, suggesting that MnCoO has a direct band gap that reduced with the CNT support. The photocatalytic activity of MnCoO/CNTs was examined for the degradation of methyl orange dye with an efficiency of ∼90.97% over 0.6 g L −1 within 50 min under UV irradiation. In the larvicidal activity, the micrograph images revealed the impact of the nanoflake particles on the 4th instar larvae, where the enzymatic activity of esterases acetylcholinesterase, α- and β-carboxylesterase, and transaminases drastically decreased with the MnCoO/CNT ratio.